A Ketogenic Diet and the Treatment of Autism Spectrum Disorder - Li, Qinrui; Liang, Jingjing; Fu, Na; Han, Ying; Qin, Jiong (Frontiers in Pediatrics, 2021)
Autism spectrum disorder (ASD) is characterized by stereotyped behavior and deficits in communication and social interaction. There are no curative treatments for children with ASD. The ketogenic diet (KD) is a high-fat, appropriate-protein and low-carbohydrate diet that mimics the fasting state of the body, and is proved beneficial in drug resistant epilepsy and some other brain diseases. An increasing number of studies demonstrated that a KD improved autistic behavior, but the underlying mechanisms are not known. We reviewed the neuroprotective role of a KD in ASD, which is likely mediated via improvements in energy metabolism, reductions in antioxidative stress levels, control of neurotransmitters, inhibition of the mammalian target of rapamycin (mTOR) signaling pathway and modulation of gut microbiota. A KD is likely a safe and effective treatment for ASD.